Becoming Bilingual Language Acquisition in a Bilingual Community - Lyon, Jean (Bilingual Education & Bilingualism, 1996)
This book is a longitudinal study of how children learn to use more than one language which addresses bilingual language development within families. It aims to examine how young children become bilingual, and to show what factors predict early childhood bilingualism